Answers

2015-11-08T20:21:31+05:30
Formula to be applied : cosA+cosB= 2cos(A+B/2).cos(A-B/2)
cos40+cos80+cos120= 2cos(80+40/2).cos(80-40/2) + cos(160)
                               =2cos(180/2).cos(40/2) + cos(160)
                               =2cos(60).cos(20) +cos(160)
                               = 2(1/2). cos(20) + cos(160)    [Since cos(60)=1/2]
                                =cos(20) + cos(160)
                                =2cos(160+20/2).cos(160-20/2)
                                =2cos(90).cos(70)                 [Since cos(90)=0]
                                =0
1 1 1